Local stress gradient approach for multiaxial fatigue behaviour assessment of high strength steels in occurrence of defects. (2018) - Pennec, Fabienne; Niamchaona, Wichian; Tihay, Kevin; Duchet, Michel; Weber, Bastien; Robert, Jean-Louis
Abstract: This study is dedicated to the effect of surface defects on the fatigue behaviour of high strength steels and the evaluation of their sensitivity. For that purpose, defects were introduced by Electro-Discharge Machining (EDM) on the edge of sheet metal test samples. Different defect depths are tested on high strength steel grades. A stress-based multiaxial fatigue life prediction method is then developed to assess the fatigue life. Input data are cyclic stress tensor states at the notch root that are calculated by a FEM analysis using the open-source Salome-meca software. In fact elastic–plastic numerical simulations were performed for each defect geometry to determine stresses distribution around the defect. A new class of multiaxial fatigue criteria extended from classical formulation to new ones with stress gradient terms related to the normal stress component is formulated. The Fogue integral approach based criterion is used since it is proved to give pertinent prevision under rotating principal stress directions multiaxial loading. For any material plane P the local stress gradient in its normal direction is calculated by parabolic interpolation and integrated to the normal stress component within the multiaxial fatigue criterion. For investigated multiaxial criteria, accounting for stress gradient effect is assessed from the experimental campaign results on two very high strength steel grades with occurence of surface defects.